Authentic cuisine as the basis of the gastronomic tourism market development of Transcarpathia (Economics and region, 2023)
Gastronomic tourism provides a great opportunity for economic growth in rural areas, social stability and well-being of the community, responsible consumption and production. It greatly contributes to the preservation of cultural heritage and is a way of identifying the nation. The lack of season events and the recognition of local cuisine as the main resource add additional value to its development. At the same time, if there is authentic cuisine, not always a destination can become a center of gastronomic tourism. The article analyzes what is needed for its development and under what conditions Transcarpathia can become a gastronomic tourist center. It has been established that gastronomy can act as a tourist resource if authentic local cuisine is preserved, the gastronomic infrastructure is sufficiently developed, and there is appropriate marketing and public-private partnership. Due to the historical development of the region, Transcarpathian cuisine is multicultural and unique, unusual for neighboring areas. At the same time, it needs research, preservation, protection and popularization, and although the first steps in this direction have been taken, they are not enough. The gastronomic infrastructure of the region is poorly developed. The offer of authentic dishes in local restaurants and cafes is limited. Dishes are positioned by origin (Hungarian, Czech, Ukrainian, and other cuisines), the brand "Transcarpathian cuisine" has not been formed. Even a loyal consumer knows on average only 3 local dishes (bograch, banosh and mushroom soup) and cannot name a restaurant of Transcarpathian cuisine. There is only one local tour operator in the gastronomic market of Transcarpathia. Gastronomy of the region is not an independent tourist product, it acts as a supplement to other services (medical, recreational or educational). At the same time, considerable experience has been accumulated in organizing one-time gastronomic tours and gastronomic events. The future of the gastronomic tourist market in the region depends on the effective partnership of representatives of state authorities, local self-government bodies, public organizations, business and science, which is lacking in the region nowadays.
Keywords: Transcarpathian cuisine; gastronomic tourism of Transcarpathia; authentic cuisine of Transcarpathia; market of gastronomic tourism